Antecedents Effect of Green Business Strategy on Business Performance in Creative SME (Fashion) in Bantul Regency - Setyawan Budhidarma (CV. Strata Persada Academia, 2023)
This study aims to assess the performance of creative SME (fashion) firms geared toward the environment. This study focuses on creative SME (fashion) that are implementing green business strategies. To test the hypothesis, the researcher use SEM (Structural Equation Modeling) based on the PLS (Partial Least Squares) technique. The researchers gathered information by delivering questionnaires to 94 creative SME (fashion) in Bantul Regency. Researchers delivered questionnaires to creative SME (fashion) spread throughout many sub-districts and hubs of natural batik artisans as well as organic leather craftsmen in Bantul Regency. The results of this research show that the green business strategy can positively and significantly mediate the association between environmental orientation and business performance. Despite the fact that the results of assessing the association between environmental orientation and business performance of creative SME (fashion) in Bantul Regency are unfavorable and insignificant. Nonetheless, creative SME (fashion) in Bantul Regency must remain optimistic about developing their environmentally friendly because SME can employ inventions and knowledge to enhance and create products, environmentally friendly processes to meet potential markets, and environmentally friendly customer needs. They will be advantageous in a more environmentally friendly industrial period in the future